Mitoferrin modulates iron toxicity in a Drosophila model of Friedreich׳s ataxia - Navarro, Juan Antonio; Metzendorf, Christoph (Free radical biology and medicine, 2015)
Friedreich׳s ataxia is the most important recessive ataxia in the Caucasian population. Loss of frataxin expression affects the production of iron-sulfur clusters and, therefore, mitochondrial energy production. One of the pathological consequences is an increase of iron transport into the mitochondrial compartment leading to a toxic accumulation of reactive iron. However, the mechanism underlying this inappropriate mitochondrial iron accumulation is still unknown. Control and frataxin-deficient flies were fed with an iron diet in order to mimic an iron overload and used to assess various cellular as well as mitochondrial functions. We showed that frataxin-deficient flies were hypersensitive toward dietary iron and developed an iron-dependent decay of mitochondrial functions. In the fly model exhibiting only partial frataxin loss, we demonstrated that the inability to activate ferritin translation and the enhancement of mitochondrial iron uptake via mitoferrin upregulation were likely the key molecular events behind the iron-induced phenotype. Both defects were observed during the normal process of aging, confirming their importance in the progression of the pathology. In an effort to further assess the importance of these mechanisms, we carried out genetic interaction studies. We showed that mitoferrin downregulation improved many of the frataxin-deficient conditions, including nervous system degeneration, whereas mitoferrin overexpression exacerbated most of them. Taken together, this study demonstrates the crucial role of mitoferrin dysfunction in the etiology of Friedreich׳s ataxia and provides evidence that impairment of mitochondrial iron transport could be an effective treatment of the disease.